RNA Delivery via DNA-Inspired Janus Base Nanotubes for Extracellular Matrix Penetration - Sands, Ian (MRS Adv, 2020)
RNA delivery into deep tissues with dense extracellular matrix (ECM) has been challenging. For example, cartilage is a major barrier for RNA and drug delivery due to its avascular structure, low cell density and strong negative surface charge. Cartilage ECM is comprised of collagens, proteoglycans, and various other noncollagneous proteins with a spacing of 20nm. Conventional nanoparticles are usually spherical with a diameter larger than 50–60nm (after cargo loading). Therefore, they presented limited success for RNA delivery into cartilage. Here, we developed Janus base nanotubes (JBNTs, self-assembled nanotubes inspired from DNA base pairs) to assemble with small RNAs to form nano-rod delivery vehicles (termed as “Nanopieces”). Nanopieces have a diameter of ~20nm (smallest delivery vehicles after cargo loading) and a length of ~100nm. They present a novel breakthrough in ECM penetration due to the reduced size and adjustable characteristics to encourage ECM and intracellular penetration.